Analyzing the Empowerment Reality of National Team Coaches for Some Individual Olympic Games" - Abdel Khaleq, Sajjad Abdel Wahid; Hussein, Hussein Khamis; Muhammad, Muhammad Qusay (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in the subject of empowerment for the national teams' coaches for some individual Olympic games, and the importance of this topic lies in developing teams and examining the reality of empowerment and analyzing it scientifically based on the results that this research will present , as well as the sample on which this research will be held as a distinct sample (coaches of some individual and Olympic games). The latter would be responsible for the results of our teams in international sports forums, The aim of the research is to identify the reality of empowerment among coaches of national teams for some individual Olympic games, and the sample is consisted of national team coaches (the first coach) for some individual Olympic games (boxing, Weightlifting, wrestling, judo, track and field, gymnastics, swimming); these coaches have been assigned in the years (2017, 2018, 2019), and they numbered (57).The research tool for gathering information has been a questionnaire prepared by researchers and subjected to scientific conditions and presented to experts until it became its final form to solve the research problem after identifying the results that have been processed with the statistical program (SPSS). The researchers have reached several results, the most important of which is that the administration used by unions is a bureaucratic administration believing to restrict authority to the hands of senior management, and that all areas of empowerment (information, strength sharing, development and training) need to be strengthened, and one of the most important recommendations recommended by researchers is to set clear and known standards for everyone about everything related to choosing (coach of the national team, assistants, players, camps, training rooms, equipment, tournaments, friendly matches) and other logistical matters.